Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7150/ijms.73701
|View full text |Cite
|
Sign up to set email alerts
|

Atranorin driven by nano materials SPION lead to ferroptosis of gastric cancer stem cells by weakening the mRNA 5-hydroxymethylcytidine modification of the Xc-/GPX4 axis and its expression

Abstract: Gastric cancer is a highly malignant tumor. Gastric cancer stem cells (GCSCs) are the main causes of drug resistance, metastasis, recurrence, and poor prognosis. As a secondary metabolite of lichen, Atranorin has a variety of biological effects, such as antibacterial, anti-inflammatory, analgesic, and wound healing; however, its killing effect on GCSCs has not been reported. In this study, we constructed Atranorin complexes comprising superparamagnetic iron oxide nanoparticles (SPION) (Atranorin@SPION). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The killing effect of atranorin on gastric cancer was also studied using complexes formed by superparamagnetic iron oxide nanoparticles (SPION) and atranorin. In vitro results on gastric cancer stem cells showed a reduction in proliferation, invasion, and tumorigenicity by reducing the expression of members of the Xc-/GPX4 axis and their mRNA 5-hydroxymethylcytidine modification and by inducing ferroptosis [ 54 ].…”
Section: Pharmacological Activity Of Lichen Depsides and Tridepsidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The killing effect of atranorin on gastric cancer was also studied using complexes formed by superparamagnetic iron oxide nanoparticles (SPION) and atranorin. In vitro results on gastric cancer stem cells showed a reduction in proliferation, invasion, and tumorigenicity by reducing the expression of members of the Xc-/GPX4 axis and their mRNA 5-hydroxymethylcytidine modification and by inducing ferroptosis [ 54 ].…”
Section: Pharmacological Activity Of Lichen Depsides and Tridepsidesmentioning
confidence: 99%
“…Comparing the effects of atranorin on normal mammary epithelial NMuMG cells and 4T1 cancer cells, it was observed that 4T1 cells were more sensitive to atranorin, reducing the clonogenic ability of carcinoma (75 µM), inducing apoptosis mediated by caspase-3 activation and poly ADP ribose polymerase (PARP) cleavage, and enhancing the depletion of Bcl-xL protein [ 57 ]. Moreover, atranorin SPION complexes showed tumorgenicity reduction in NOD-scid mice [ 54 ].…”
Section: Pharmacological Activity Of Lichen Depsides and Tridepsidesmentioning
confidence: 99%
“…This occurs through a combined therapeutic effect involving DOX chemotherapy and magnetic MSNs MFH under the influence of an alternating magnetic field. 371 Moreover, antibodymodified NPs, particularly those targeting lung CSCs, have shown enhanced cellular uptake and prolonged tumor accumulation, effectively eliminating up to 98% of lung CSCs in in vivo models. The combination of hyperthermia and chemotherapy exhibited significant inhibition of tumor growth and metastasis in mice carrying lung CSC xenografts, with minimal side effects and adverse reactions.…”
Section: Innovative Approachesmentioning
confidence: 99%
“…Biomimetic magnetic NPs have exhibited the ability to induce apoptosis in stress‐escape CSCs and impede their proliferation and metastasis both in vitro and in vivo. This occurs through a combined therapeutic effect involving DOX chemotherapy and magnetic MSNs MFH under the influence of an alternating magnetic field 371 . Moreover, antibody‐modified NPs, particularly those targeting lung CSCs, have shown enhanced cellular uptake and prolonged tumor accumulation, effectively eliminating up to 98% of lung CSCs in in vivo models.…”
Section: Targeting Csc Signaling Pathwaysmentioning
confidence: 99%
“…Several studies have improved the physicochemical properties and bioavailability of natural products by developing novel drug delivery systems and carriers (Z. Ni, Nie, et al, 2022;Z. Zhang, Ji, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%